Accounting Treatment of Happy Hour in Evaluating the Performance of the Food & Beverage Department at Hotel X - Ni Kadek Desi Sari; Anak Agung Istri M. Septiviari; I Gusti Ngurah Agung Wiryanata (Transpublika Publisher, 2025)
This study discusses the accounting treatment of the happy hour program in assessing the performance of the Food & Beverage Department at Hotel X. Happy hour is a marketing tactic that aims to increase beverage sales during off-peak hours by offering special promotions, such as buy 1 get 1 free. The research method uses a descriptive qualitative approach with data collection through interviews, observations, and documentation studies and utilizes secondary data sources and primary data. The results showed that the accounting treatment of happy hour program revenue is recorded in the other expense account in the Sales & Marketing department, in accordance with PSAK No. 72 of 2020 and USALI Schedule 7 - Sales & Marketing. Revenue is measured based on predetermined menu prices, as well as market and competitor survey analysis. Presentation is presented in the income statement, and disclosure of this program revenue is disclosed in the notes to the financial statements. The happy hour program has a positive operational impact on the performance of the Food & Beverage department in terms of cost efficiency, sales volume, and service quality.